Estudio e implementación de un sistema HACCP para las líneas de producción de norbixina y carmín de la empresa Imbarex S.A. - Tello Tamayo, Fernando (2021)
The present work is a study, and the subsequent implementation, of a hazard analysis system and critical control points HACCP, which was carried out in the company that produces natural dyes called Imbarex SA. This study was executed in two main production lines: natural dyes made from the cochineal insect (Dactilopus cocus costa) and natural dyes made from the annatto seed (Bixa orellana). The activities were carried out during 2011 in the months from May to December, during which time, as production assistant; different studies in the company were done in its administrative and productive operations, in such a way that a food safety management system could be implemented for the carmine and norbixin production lines. During the hazard analysis of the HACCP matrices, it was found that the main biological hazard is salmonella sp in both production lines. Critical control limits and methods for such controls were established for these critical control points CCP. The control parameters of the critical points are in concordance of temperature and time, thus having temperatures of 90 ° C to 120 ° C for carmine products; and from 90 ° C to 95 ° C for norbixin products. By the end of the year, in December 2011, the HACCP certification audit was carried out. In the aforementioned certification, 2 minor nonconformities were found, which were rectified and thus the respective HACCP certificate was awarded to the company. This certification was made with the SGS Company. When evaluating the cost-benefit of the work performed, it was calculated an investment of approximately S/ 58,630.00 new soles with returns greater than S / 200,000.00 new soles in the first year thanks to the achievement and the signing of new sales contracts.